2015
DOI: 10.1128/jcm.01432-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Two Rapid Tests for Detection of HIV-1 and -2 in High- and Low-Prevalence Populations in Nigeria

Abstract: The availability of reliable human immunodeficiency virus types 1 and 2 (HIV-1/2) rapid tests in resource-limited settings represents an important advancement in the accurate diagnosis of HIV infection and presents opportunities for implementation of effective prevention and treatment interventions among vulnerable populations. A study of the potential target populations for future HIV vaccine studies examined the prevalence of HIV infections at six selected sites in Nigeria and evaluated the use of two rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
1
19
1
1
Order By: Relevance
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported using a suboptimal testing strategy that differed from the WHO recommendations [5,8,1114,16,2230,3234,36–39,4244,49,51,53,59,62,64–66,68,72,75]. Suboptimal testing strategies included using a highly specific first-line test and highly sensitive second-line test [14,33,39,55], using a single RDT for HIV-positive diagnoses [11,66,72], using a high prevalence testing strategy in a low prevalence setting [16,49], using a parallel testing algorithms and a tiebreaker testing strategy (where a third assay is used to resolve discrepant test results and rule in HIV infection) [5,12,13,16,24,25,2730,32,34,36,37,68].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stat-Pak) is used as the tie-breaker [31]. Some clinical settings prefer the use of parallel HIV testing algorithm prior confirmatory procedures [32] while others make enzyme-linked immuno-sorbent assay (ELISA) technique the starting point for HIV diagnosis [33] There is virtual lack of data on the rapid HIV antibody testing based on serial algorithm II validated with molecular techniques (such as real-time polymerase chain reaction) in HIV diagnosis especially in Ekiti state and that requires evidence-based baseline study.…”
Section: Introductionmentioning
confidence: 99%